A strategy for the provision of sustainable water supply in the Upper Tsitsana Village : a community development project - Mdletye, A. N.(Alpheus Nyaniso) (Stellenbosch : Stellenbosch University, 2012)
Study project (M.P.A.) -- University of Stellenbosch, 1998.